2014
DOI: 10.1109/lpt.2014.2317702
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic Temperature Measurement Using Rayleigh Backscattering Spectra Shift by OFDR

Abstract: We present a method to realize temperature variation measurement in the cryogenic environment (e.g., at 76 K) using Rayleigh backscattering spectra (RBS) shift in standard single mode optical fiber by optical frequency-domain reflectometry. By analyzing the relationship of effective sensing segment size of fiber (or sensing spatial resolution), minimal measurable temperature variation, and temperature response of RBS shift, we found minimal measurable temperature variation in the cryogenic environment can be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Due to the grating process, FBG fibers are also more expensive. Conversely, measurements using Rayleigh backscattering can be taken with low-cost standard single-mode optical fibers [19], but data processing is more elaborate for this method. At the test rig 14 Rayleigh fibers with a length up to 20 m are applied, allowing temperature measurements between -196 °C and 50 °C with an accuracy of 3 °C at intervals of a few mm along the fibers [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the grating process, FBG fibers are also more expensive. Conversely, measurements using Rayleigh backscattering can be taken with low-cost standard single-mode optical fibers [19], but data processing is more elaborate for this method. At the test rig 14 Rayleigh fibers with a length up to 20 m are applied, allowing temperature measurements between -196 °C and 50 °C with an accuracy of 3 °C at intervals of a few mm along the fibers [7].…”
Section: Methodsmentioning
confidence: 99%
“…Distributed temperature measurements using optical fibers have been successfully applied in numerous different fields such as long-distance environmental monitoring [20] and nuclear power plants [21]. Also, fiber optical sensors have been used under cryogenic conditions [19], especially in the area of superconducting technology (e.g., [22]). Reviews of distributed temperature-sensing technology and applications can be found in [20,23,24].…”
Section: Methodsmentioning
confidence: 99%
“…Once the process is not handled properly, transmission loss will increase and distributed fiber strain measurement will be exposed to ultra-low temperatures [6] . So far, there are some reports on distributed optical fiber temperature sensing in ultra-low temperature environments, while strain measurements in ultralow temperature environments have been rarely reported [7][8] . The cross sensitivity of distributed optical fiber to temperature and strain restricts the application of this technique in the field of strain sensing under ultra-low temperature [9] .…”
Section: Introductionmentioning
confidence: 99%
“…The spectra shift of the Optical Frequency Domain Reflectometry (OFDR) was used to monitor a cryogenically cooled cable at 15 K [13]. The same technology was demonstrated to have a similar sensitivity at 77 K and room temperature in a subsequent study [14]. More recently, the OFDR technology was tested with an optical fiber embedded inside a REBCO CORC ® cable for quench detection [15] [16].…”
Section: Introductionmentioning
confidence: 99%